2020
DOI: 10.1063/1.5119187
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing bifurcation diagrams only from time-series data generated by electronic circuits in discrete-time dynamical systems

Abstract: Bifurcation-diagram reconstruction estimates various attractors of a system without observing all of them but only from observing several attractors with different parameter values. Therefore, the bifurcation-diagram reconstruction can be used to investigate how attractors change with the parameter values, especially for real-world engineering and physical systems for which only a limited number of attractors can be observed. Although bifurcation diagrams of various systems have been reconstructed from time-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In the BD reconstruction, time-series predictors are trained to model the obtained time-series data sets of all components, and the method allows the attractors of all components to be estimated when the bifurcation parameter values are changed. We reconstructed the BDs for various systems and numerical conditions using time-series data sets of a component in [8][9][10][11][12][13][14]. In this study, we show that the reconstruction requires a shorter length of training data when using time-series data sets of all components than when using the time series of only one component, compared by the previous studies.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…In the BD reconstruction, time-series predictors are trained to model the obtained time-series data sets of all components, and the method allows the attractors of all components to be estimated when the bifurcation parameter values are changed. We reconstructed the BDs for various systems and numerical conditions using time-series data sets of a component in [8][9][10][11][12][13][14]. In this study, we show that the reconstruction requires a shorter length of training data when using time-series data sets of all components than when using the time series of only one component, compared by the previous studies.…”
Section: Introductionmentioning
confidence: 66%
“…Given its extremely high training speed and good generalization, we use the ELM as a time-series predictor. In previous work, we showed that the ELM is useful for reconstructing BDs [8][9][10][11][12][13].…”
Section: Extreme Learning Machinementioning
confidence: 99%
See 1 more Smart Citation
“…In order to perform the calculations, special software dedicated to the measuring platform was written, described in detail in the section titled: -Description of the measuring platform.‖ The main solver performing calculations was designed in the form of two separate CUDA kernels (kernel is a function performed on the CUDA device). The task of the first kernel is to solve the system of differential equations using the Runge-Kutta fourth-order method (1).…”
Section: Implementation Of Calculationsmentioning
confidence: 99%
“…This paper uses three-dimensional approach to bifurcation diagrams, while the bifurcation diagrams usually presented in the literature take a single-parameter or much less often twoparameter form [1][2][3][4][5][6]. The use of a three-dimensional approach to bifurcation involves the presentation of a point cloud in space.…”
Section: Introductionmentioning
confidence: 99%